Des maternelles jurés au Prix des Incorruptibles : une critique littéraire en herbe ? - Bérénice Waty (Strenae)
Giving children the opportunity to explain what happens between them and the books or stories they read allows us to grasp their relationships to and representations of the reading, and to understand how children enter the world of books. Using ethnographic fieldwork from a kindergarten class participating in the Prix des Incorruptibles, we will see how the discovery and process of imitating professional and everyday jurors of literary prizes assists a reader's in-progress journey, by allowing young children to make their own discoveries and take ownership.